Functionalized Boron Carbide Nanoparticles as Active Boron Delivery Agents Dedicated to Boron Neutron Capture Therapy - Rudawska A; Szermer-Olearnik B; Szczygieł A; Mierzejewska J; Węgierek-Ciura K; Żeliszewska P; Kozień D; Chaszczewska-Markowska M; Adamczyk Z; Rusiniak P; Wątor K; Rapak A; et al. (International Journal of Nanomedicine)
Anna Rudawska,1 Bożena Szermer-Olearnik,1 Agnieszka Szczygieł,1 Jagoda Mierzejewska,1 Katarzyna Węgierek-Ciura,1 Paulina Żeliszewska,2 Dawid Kozień,3 Monika Chaszczewska-Markowska,1 Zbigniew Adamczyk,2 Piotr Rusiniak,4 Katarzyna Wątor,4 Andrzej Rapak,1 Zbigniew Pędzich,3 Elżbieta Pajtasz-Piasecka1 1Hirszfeld Institute of Immunology and Experimental Therapy, Polish Academy of Sciences, Wrocław, Poland; 2Jerzy Haber Institute of Catalysis and Surface Chemistry, Polish Academy of Sciences, Krakow, Poland; 3Depatment of Materials Science and Ceramics, AGH University of Krakow, Krakow, Poland; 4Department of Geology, Geophysics and Environmental Protection, AGH University of Krakow, Krakow, PolandCorrespondence: Bożena Szermer-Olearnik, Hirszfeld Institute of Immunology and Experimental Therapy, Polish Academy of Sciences, Weigla 12, 53-114, Wrocław, Poland, Tel +48 713371172 ext. 242, Email bozena.szermer-olearnik@hirszfeld.plIntroduction: Boron neutron capture therapy (BNCT) is a promising targeted radiotherapy that enables the treatment of cancers at the cellular level. The crucial aspect of BNCT are boron carriers, which should selectively reach cancer cells by delivering high concentrations of boron. Therefore, we propose the use of boron carbide (B4C) nanoparticles functionalized with antibodies directed against receptors overexpressed in cancer cells, such as the low-density lipoprotein receptor (LDLR) and the epidermal growth factor receptor (EGFR).Methods: Hydrodynamic diameter measurements confirmed the stability of functionalized B4C nanoparticles in culture media during biological tests lasting up to 72 hours. The toxicity of the nanoparticles was assessed using the MTT assay and BrdU cell cycle assay on three types of cancer cells (PC-3, T98G, and SCC-25) with different levels of LDLR and EGFR surface expression. The uptake of functionalized B4C nanoparticles by cancer cells was assessed based on flow cytometry, fluorescence microscopy, and holotomography. Boron concentrations in cancer cells were quantified via ICP-MS.Results: Functionalized B4C nanoparticles showed even 2-fold higher interaction with SCC-25 cells characterized by the highest surface expression of both receptors than with PC-3 and T98G cells. Holotomographic imaging confirmed the greater intracellular uptake of functionalized B4C nanoparticles compared to unmodified B4C, providing further evidence for the selective targeting of boron to cancer cells. ICP-MS analyses showed that B4C anti-LDLR nanoparticles were the most effective in delivering a high boron concentration to cancer cells. Particularly in SCC-25 cells, the concentration was 9.58 ± 2.6 mg/L boron per million cells. The highest uptake by these cells was associated with a decrease in viability to 63% and a slight reduction in the percentage of cells in S phase after 24-hour exposure.Conclusion: Stable complexes of antibody-functionalized B4C nanoparticles were successfully obtained, demonstrating increased tropism towards cancer cells overexpressing LDLR and EGFR. Keywords: boron carbide, nanoparticles, targeted functionalization, anticancer therapy, BNCT